(untitled) (International Journal of Engineering and Computer Science, 2016)
Cloud computing is an evolving data interactive paradigm to perceive user’s data remotely stored in an online cloud server. It provides great benefits for the users to enjoy the on-demand cloud applications without considering the local infrastructure restrictions. During the data accessing, different users may be in alliance, and thus data sharing becomes remarkable to achieve productive advantages. The existing security solutions mainly focus on the authentication to realize that a users destitution data cannot be illegally accessed, but neglect a minute privacy matter during a user challenging the cloud server to request other users for data sharing. The challenged access request itself may disclose the users privacy no matter whether or not it can obtain the data access permissions. The proposed system suggest a multi-user sharing privacy-preserving authentication protocol to address above privacy issue for cloud storage.